(14/3)x=-126/11

Simple and best practice solution for (14/3)x=-126/11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (14/3)x=-126/11 equation:


x in (-oo:+oo)

(14/3)*x = -126/11 // + -126/11

(14/3)*x-(-126/11) = 0

(14/3)*x+126/11 = 0

14/3*x+126/11 = 0 // - 126/11

14/3*x = -126/11 // : 14/3

x = -126/11/14/3

x = -27/11

x = -27/11

See similar equations:

| 4(n+4)=-2+7n | | 4.2x+4=25 | | 5(x)X(25)2x=5 | | (957/14)x=18 | | 2(3x+5)+2(8x-7)=180 | | 112x5/14 | | (22/3)x=7 | | 5x-2=41 | | 9e^4x=196 | | 5g+3.29=25.24 | | .069x+x=20 | | 4.905x*x=11 | | 127+x+(x-10)+(x-3)=180 | | .06x-2=3+0.4x | | -48+11n-20n+12=0 | | 6a+18-10=-2a-8 | | -45=-(1+2n)-6+(4-2n) | | -8(6-8b)+3(1+6b)=37 | | 8y-6=34 | | xsquared+21x+20= | | x+21x+20= | | 127+x+(x-10)+(x-3)=360 | | 293+(2x-5)+x=360 | | 5=1/1-0.25*(1-x) | | 5x-2x=-28 | | 2a+3b+1-6b+a+5= | | X-.15x=62 | | (5x-13)+(2x)+(4x+13)+x=360 | | 12-2(4+4x)=-8x+4 | | 4=1/1-0.8*(1-x) | | X-y-z=-7 | | 4x-8=-4(2x-3) |

Equations solver categories